Phosphate and Nitrate Uptake Dynamics in Palmaria palmata (Rhodophyceae): Ecological and Physiological Aspects of Nutrient Availability. Issue 5 (15th June 2020) - Lubsch, Alexander; Timmermans, Klaas R.
Abstract : Uptake dynamics of dissolved inorganic phosphate (DIP) and dissolved inorganic nitrate (DIN) in young Palmaria palmata ( n = 49), cultivated in a range of DIP concentrations (0.0–6.0 µmol · L −1 ) and nonlimiting DIN concentration (50 µmol · L −1 ) under fully controlled laboratory conditions, were quantified in a 'pulse‐and‐chase' approach over 5 weeks. Two different uptake rates were specified: (1) surge uptake (VS ) after starvation and (2) maintenance uptake with filled nutrient pools (VM ). VS for DIP of 1.57 ± 0.29 µmol · cm −2 · d −1 and DIN of 15.6 ± 4.3 µmol · cm −2 · d −1, as well as VM for DIP of 0.57 ± 0.22 µmol · cm −2 · d −1 and DIN of 5.6 ± 2.1 µmol · cm −2 · d −1 were calculated. In addition, an absolute size of the internal storage capacity (ISC) for DIP of 22 µmol · cm 2 and DIN of 222 µmol · cm 2 was determined. A DIP‐to‐DIN uptake ratio of 1:10 under VM showed a weekly rhythmic uptake pattern, highlighted by a high correlation between DIP and DIN uptake (R = 0.943). VS for DIN did not occur under DIP depletion, but uptake rates increased with increasing DIP availability. Hence, DIP availability limited access to DIN, which was also reflected by total dissolvable protein concentrations in sporophytes, which ranged from 10.2 ± 2.5% to 24.6 ± 8.0% dry weight depending on DIP availability. Similarly, total dissolvable carbohydrate concentration ranged from 22.1 ± 3.6% to 54.3 ± 12.3% dry weight. The data presented in this study open further insight into ecological and physiological aspects of nutrient availability in P. palmata and allow for an optimization in cultivation.